Understanding Suicide - Fincham, B. author. aut Link
VII, 203 p.
Keywords: Sociologists have debated suicide since the early days of the discipline. This book assesses that body of work and breaks new ground through a qualitatively-driven, mixed method 'sociological autopsy' ofone hundredsuicides that explores what can be known about suicidal lives.